Protocols for Visualizing Steroidogenic Organs and Their Interactive Organs with Immunostaining in the Fruit Fly Drosophila melanogaster - Imura, Eisuke (J Vis Exp, 2017)
In multicellular organisms, a small group of cells is endowed with a specialized function in their biogenic activity, inducing a systemic response to growth and reproduction. In insects, the larval prothoracic gland (PG) and the adult female ovary play essential roles in biosynthesizing the principal steroid hormones called ecdysteroids. These ecdysteroidogenic organs are innervated from the nervous system, through which the timing of biosynthesis is affected by environmental cues. Here we describe a protocol for visualizing ecdysteroidogenic organs and their interactive organs in larvae and adults of the fruit fly Drosophila melanogaster, which provides a suitable model system for studying steroid hormone biosynthesis and its regulatory mechanism. Skillful dissection allows us to maintain the positions of ecdysteroidogenic organs and their interactive organs including the brain, the ventral nerve cord, and other tissues. Immunostaining with antibodies against ecdysteroidogenic enzymes, along with transgenic fluorescence proteins driven by tissue-specific promoters, are available to label ecdysteroidogenic cells. Moreover, the innervations of the ecdysteroidogenic organs can also be labeled by specific antibodies or a collection of GAL4 drivers in various types of neurons. Therefore, the ecdysteroidogenic organs and their neuronal connections can be visualized simultaneously by immunostaining and transgenic techniques. Finally, we describe how to visualize germline stem cells, whose proliferation and maintenance are controlled by ecdysteroids. This method contributes to comprehensive understanding of steroid hormone biosynthesis and its neuronal regulatory mechanism.